Cytotoxicity and thrombolytic potential of seven different medicinal plant leaves extract - Azad, A.K.; Sarker, Md. Zaidul Islam; Helal Uddin, A.B.M.; Alaama, Mohamed; Abdullah, J. (2018)
Background: In practice, either the herbs themselves or the crude extracts are used for traditional remedies but not the isolated molecules. Therefore, the importance of toxicity and clot lysis study of the crude extract is beyond description. Objective: The aim of our study was to find out the preliminary cytotoxic and thrombolytic effect of the seven selected medicinal plant leaves extract. Methods: Cold maceration was performed using ethanol for extraction purposes. The cytotoxicity study was done by using brine shrimp nauplii (Artemia salina) and MTT assays by using MCF-7 cell line. Result: In the cytotoxic activity, out of the seven leaves extract three of them exhibited stronger brine shrimp lethality with 4 TH PHARMACEUTICAL RESEARCH CONFERENCE 2018 Challenging The Inquisitive Minds: Frontier Of The Future 24 – 26 August 2018 | Cyberjaya, Malaysia